Effect of thermal processes on Al thin film in the present of nitrogen (N2) gas - Riyaz Ahmad, Mohamed Ali; Ahmad Nasrull, Mohamed; Nafarizal, Nayan (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.